2010
DOI: 10.1093/aje/kwq244
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Estimating Model-Adjusted Effect-Measure Modification Using Marginal Structural Models and Complex Survey Data

Abstract: Recently, it has been shown how to estimate model-adjusted risks, risk differences, and risk ratios from complex survey data based on risk averaging and SUDAAN (Research Triangle Institute, Research Triangle Park, North Carolina). The authors present an alternative approach based on marginal structural models (MSMs) and SAS (SAS Institute, Inc., Cary, North Carolina). The authors estimate the parameters of the MSM using inverse weights that are the product of 2 terms. The first term is a survey weight that adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…Finally, we conducted a test for homogeneity of the risk difference across the three age groups. These analyses used inverse weighting to adjust for confounding and selection bias introduced by the complex survey design [5]; analyses were completed using SAS 9.2 (SAS Institute Inc., Cary, NC). This study was approved by the University of Florida's Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we conducted a test for homogeneity of the risk difference across the three age groups. These analyses used inverse weighting to adjust for confounding and selection bias introduced by the complex survey design [5]; analyses were completed using SAS 9.2 (SAS Institute Inc., Cary, NC). This study was approved by the University of Florida's Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the weighting for the naïve models is composed of only the PSID longitudinal survey weights. For both strategies, we use Huber–White sandwich estimators to obtain robust standard errors (Brumback, Bouldin, Zheng, Cannell, & Andresen, 2010). …”
Section: Inverse Probability Of Treatment Weightingmentioning
confidence: 99%
“…Recently, marginal structural models and inverse probability-of-treatment weighting have been used to examine effect modification. 19,20 This approach is effective in studying dynamic life course developmental processes, where the value of either exposures or effect modifiers is known to be time varying. 21 Berkey et al demonstrated the use of multilevel random-effects models for estimating effect modification across places, 22 an approach well illustrated in an analysis of EM effect modification in 29 European cities in the APHEA2 project.…”
Section: Complex Interactions and Synergiesmentioning
confidence: 99%